2021
DOI: 10.3389/fimmu.2021.680407
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in Acral and Mucosal Melanoma: Current Status and Future Directions

Abstract: Acral and mucosal melanomas are extremely rare in Caucasians; however, they are the predominant melanoma subtypes in Asians and other non-Caucasian populations. Acral and mucosal melanomas share many clinicopathological features, including aggressive phenotypes, similar genetic landscapes, and grim prognoses. In spite of advances in melanoma management, patients with acral and mucosal melanomas show limited benefit from current therapies. The rarity of these subtypes of melanoma is a significant factor contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
71
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 135 publications
(171 reference statements)
0
71
0
1
Order By: Relevance
“…In Europe and the US, the MM often triggered by ultraviolet and occurred in the skin [ 1 ]. In China, the MM occurred in the mucous except the skin nearly 50% (51.0%, 75/147, in our data) [ 31 ]. Several studies have been reported the useful biomarkers to predict the metastasis in the MM.…”
Section: Discussionmentioning
confidence: 75%
“…In Europe and the US, the MM often triggered by ultraviolet and occurred in the skin [ 1 ]. In China, the MM occurred in the mucous except the skin nearly 50% (51.0%, 75/147, in our data) [ 31 ]. Several studies have been reported the useful biomarkers to predict the metastasis in the MM.…”
Section: Discussionmentioning
confidence: 75%
“…Compared with the excellent clinical efficacy of ICI therapy in melanoma, the investigations of its biomarkers are relatively insufficient. The data from the real world revealed that durable responses and favorable long-term outcomes are limited a proportion of melanoma ( 12 ). Thus, more attention should be paid to the discovery and establishment of novel biomarkers for selecting patients who may benefit from ICI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of immunotherapy, immune checkpoint inhibitors (ICI) therapy has been approved as the standard treatment for melanoma (4)(5)(6)(7)(8). According to the reports from multiple clinical trials (9)(10)(11)(12), the overall response rate (ORR) of PD-1 blockade with nivolumab or pembrolizumab ranged from 26% to 44%, thus indicating almost 50% of patients with severely progressed melanoma do not obtain complete or partial response, with roughly 24% reach a stable disease only. Notably, as the main subtypes of Asian patients with melanoma, only 10~20% of acral and mucosal cases can benefit from ICI therapy (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous melanoma (CM) is highly malignant, accounting for more than 80% of deaths from skin disease [ 1 , 2 ]. As of late, the incidence and mortality of CM are increasing.…”
Section: Introductionmentioning
confidence: 99%